Analisis Zakat Produktif Terhadap Indeks Kemiskinan, Nilai Material dan Spiritual Para Mustahik - Nono Hartono; Mohamad Anwar (ITB AAS INDONESIA Surakarta, 2018)
This research intend to analyze the changes of mustahik household income after receive assistance from productive zakah funds from Cirebon Zakat Center and identify the characteristics of material and spiritual values of mustahik after obtaining assistance from productive zakah funds from the Cirebon Zakat Center based on the CIBEST model. This study uses a quantitative approach with data collection techniques in the form of observation, interviews and filling out questionnaires. The statistical test and data analysis used are paired data t test and CIBEST model. The results of the study showed that mustahik household income after receiving productive zakah funds experienced a significant change. Before the assistance of zakah, the average household income of mustahik are Rp. 1,110,563, and after getting zakah the average household income of mustahik rise to Rp. 1,653,000. This means that there is an increase in the average household income of mustahik by Rp. 542,437. Based on the CIBEST model, the material and spiritual value characteristics of mustahik after assistance productive zakah funds from Cirebon Zakat Center experienced a change. After the assistance, the number of mustahik households in the category of prosperous households (quadrant I) increased by 47.50 percent. Whereas, number of mustahik households that fall into the material poor category (quadrant II) decreased by 25.00 percent. Likewise, the number of mustahik households included in the category of spiritual poor (quadrant III) and absolute poverty (quadrant IV) fell by 54.55 percent and 90.91 percent respectively.